The Kidney at the Limit: A Comprehensive Review of Exertional Rhabdomyolysis and Acute Kidney Injury in the Amateur Athlete - Tymińska, Paulina; Frączek, Julia; Borówka , Karolina; Kawka, Natalia; Górka, Piotr Artur; Kądziołka, Witold; Domagała, Szymon (Journal of Education, Health and Sport, 2026)
The modern fitness landscape has seen a significant rise in Exertional Rhabdomyolysis (ER), a potentially life-threatening condition traditionally associated with extreme endurance or military combat. As high-intensity functional training and aggressive indoor cycling become mainstream, recreational athletes are increasingly exposed to metabolic crises previously rare in the commercial gym sector. This review examines the pathophysiology of ER, beginning with the ATP depletion-calcium dysregulation cascade that leads to myocyte necrosis and the systemic release of intracellular contents. Central to the clinical concern is the "Nephrotoxic Triad" - a synergistic mechanism involving renal vasoconstriction, oxidative stress via the Fenton Reaction, and physical tubular obstruction by myoglobin casts, which precipitates Acute Kidney Injury (AKI). The article identifies a "perfect storm" of risk factors, including eccentric loading, heat strain, and the pervasive, unsupervised use of NSAIDs, which disable the kidney’s autoregulatory mechanisms. Diagnosis remains challenging, as the classic triad of symptoms is present in less than 10% of cases; thus, the review highlights the importance of serum Creatine Kinase (CK) and the emerging utility of Cystatin C as a muscle-mass-independent biomarker for renal function. Management focus is placed on aggressive, early fluid resuscitation using balanced crystalloids to induce forced diuresis. Finally, the review proposes a four-phase return-to-play protocol, emphasizing a risk-stratified approach to transition athletes safely from recovery to sport-specific activity while mitigating the long-term risks of chronic kidney disease and recurrence.